Progression of chronic kidney disease in a multi‐ethnic community cohort of patients with diabetes mellitus. Issue 8 (20th April 2013) - Dreyer, G.; Hull, S.; Mathur, R.; Chesser, A.; Yaqoob, M. M.
Abstract Aims Ethnicity is a risk factor for the prevalence of severe chronic kidney disease among patients with diabetes. We studied the effect of ethnicity on progression of chronic kidney disease in people with diabetes managed in community settings. Methods A 5‐year retrospective, community‐based cohort study of 3855 people with diabetes mellitus of white, black or South Asian ethnicity with an estimated glomerular filtration rate of < 60 ml min−1 1.73 m−2 was undertaken. From 135 general practices in east London, all cases with at least 3 years clinical data were included. Using repeated‐measures analysis, the annual decline in estimated glomerular filtration rate was calculated. Comparisons between the rate of decline in the three main ethnic groups, with and without proteinuria at baseline, were made. Results The annual adjusted decline in estimated glomerular filtration rate for this cohort was 0.85 ml min−1 1.73 m−2. The rate of chronic kidney disease progression was significantly greater in South Asian groups (–1.01 ml min−1 1.73 m−2) compared with white groups (–0.70 ml min−1 1.73 m−2) (P = 0.001). For those with proteinuria at baseline, the annual decline was greater at 2.05 ml min−1 1.73 m−2, with both South Asian and black groups having a significantly faster rate of decline than white groups. Conclusions For patients with diabetes and chronic kidney disease managed in primary care, the annual decline of renal function is less than previously thought and approximates the age‐related annual decline of 1 ml min−1 1.73 m−2. Patients with proteinuria and those of South Asian and Black ethnicity need additional monitoring as they are at greater risk of rapid chronic kidney disease progression.